A SYSTEMATIC STUDY AND META-ANALYSIS OF TUBERCULOSIS INFECTION PREVALENCE IN INDIA - Mishra, Prabhakar Bhushan; Jaiswal, Rajendra Prasad; Bhushan, Bharat (Student’s Journal of Health Research Africa, 2024)
Background and objectives One of the most common infectious agent-related causes of death worldwide is tuberculosis (TB), which is caused by Mycobacterium tuberculosis. Nevertheless, not much is currently understood regarding the prevalence of TBI in India’s various risk groups. The purpose of this systematic review and meta-analysis was to calculate the prevalence of TBI in India by risk categories, sociodemographic profile, and geographic location. Methods Through a comprehensive analysis, this study investigated the prevalence of tuberculosis infection (TBI) in India between 2013 and 2022. Following the recommendations in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), 70 papers were examined using databases such as Scopus, CINAHL, EMBASE, and MEDLINE. The holistic method provided a detailed picture of the prevalence of TBI in India by using a variety of languages and study settings. Results 70 research studies, including approximately 40 prevalence studies and approximately 30 long-term studies, were included in this paper after a review of 10,510 papers. Based on population-based sample studies, the total prevalence of tuberculosis infection (TBI) in India was 40.79 %. When highly sensitive populations were excluded from the general population, this percentage remained constant at 35.99%. T Conclusion The current thorough investigation demonstrated the high prevalence of TB infections in India, which corresponded with proactive TB infections and suggested a possible transition from latent to active TB. Notably, people living in the southern regions of the country were more likely to experience this possibility. Recommendation To assist efficient programmatic management in the pursuit of India’s TB elimination targets, this study suggests giving priority to Tuberculosis Preventive Treatment (TPT) in areas with a high prevalence of Tuberculosis Infection (TBI) and promoting a "No test, treat only" approach for resource efficiency.